REPRESENTAÇÕES SOCIAIS DE LÍNGUA E CULTURA NO ENSINO DE INGLÊS: PRODUÇÕES ACADÊMICAS EM DESTAQUE - SOUSA, ROSÁLIA WIELEWSKI DE (2022)
This dissertation analyzes academic productions that deal with social representations, language and culture about the teaching of English and aims to verify which is the concept of language and culture that predominates in the dissertations and thesis selected for this study. This is qualitative research, of bibliographic character, having as search matrix data from the CAPES platform and Google Scholar. Therefore, first I bring an overview of some understandings attributed to culture: a) the anthropological idea of culture; b) the sociological conception; and c) the postmodern meaning, according to Bhabha and Hall. Furthermore, in this work, I use the principle of social representations which, according to Moscovici, are forms of dynamic collective representations that prescribe and condition the symbolic aspects of a society. Concomitant with such ideas, it adopts the conception of language as discourse based on Bakhtin, dialoguing with the notion of language as culture according to Kramsch. And yet, starting from the current position of English as a Lingua Franca/International, I try to verify the place of culture in this status of the English language. As a theoretical basis for teaching English as a Lingua Franca, it considers the notes of McKay (2012), Jenkins (2007), Cogo (2012), Seidholfer (2005) and Pennycook (2007). Therefore, with this study it was possible to build a vision about the social representations presented by researchers regarding the cultural aspects linked to the English language and the status of English as a lingua franca, in addition to verifying how culture has been approached in the teaching of English according to the perceptions of these authors. The conclusions also indicate possibilities to expand this theme, by conducting research with groups of English-speaking students from different contexts to verify how the language/culture relationship is understood in the teaching-learning process and what imagery involves the language English for these subjects.